A look into the influence of income tax, as a tool for stimulating economic growth in Nigeria (Journal of Economic Research & Business Administration, 2022)
The study empirically examined the effect of income tax on economic growth in Nigeria. The specificobjectives are as follows: to examine how capital gain tax, company income tax and how valueadded tax effect gross domestic product in NigeriaThis study adopted ex-post facto research design. Relevant data regarding the variables under-studywere extracted from the Central Bank of Nigeria (CBN) statistical bulletin. The study period coveredTwenty-Five (25) years spanning from 1994 to 2019, while error correction model was used to analyzethe data.The findings revealed among other things that; there was presence of co-integration (long-run relationship)among the variables in the model, capital gain tax, company income tax and value added taxhave significant relationship with gross domestic product of Nigeria in the long run.Based on this, the study therefore concluded that all the variables have positive and significant effecton gross domestic product, the study recommended among other things that government shouldensure efficiency and effectiveness in the tax administration and tax compliance, also emphasis shouldbe on enhancing direct assessment through capturing every eligible taxpayer in other to boost the levelof revenue mobilization,It is recommended that government should reduce corporate tax rate rather than eliminate high corporatetax in Nigeria, lower corporate tax will increase the demand for labour which in turn raises wagesand increases consumption.Key words: Corporate Income Tax, Capital Gain Tax, Value Added Tax, Gross Domestic Product.